Assessment of nonlinear bond laws for near-surface-mounted systems in concrete elements - Ceroni, Francesca (2013)
This paper presents a numerical plane Finite Element (FE) Model for use in simulating the behaviour of different types of Near Surface Mounted (NSM) Fibre Reinforced Plastic (FRP) strengthening systems for concrete elements. Based on a nonlinear bond law for simulating the behaviour of the FRP reinforcement-adhesive-concrete interface, the model employs an interface element between the NSM FRP reinforcement and the concrete. The results of two different experimental programs, both dealing with 'bond tests' but with distinct set-ups, are briefly summarised and analysed. The main objective of this research is to assess the values of the parameters that define the nonlinear bond laws for each type of FRP reinforcement tested. This assessment was accomplished by inverse analysis, fitting numerically the pullout load–displacement curves that were experimentally recorded. The effect of bond length on different types of NSM FRP reinforcement is assessed. Finally, the bond behaviour in the transverse plane is examined too.